Construction and implementation of humanistic care with Traditional Chinese Medicine nursing interventions in orthopedic wards (骨科病房中医人文关怀护理模式构建与实施效果) - YUAN Linfeng (袁林凤); ZHANG Xuejian (张雪键); CUI Yangfang (崔杨芳); YANG Jinrui (杨金瑞) (中西医结合护理)
Objective To explore the construction and implementation effect of humanistic care with Traditional Chinese Medicine (TCM) nursing interventions in orthopedic wards. Methods Totally 120 hospitalized patients with orthopedic diseases were randomly divided into the control group and observation group, with 60 cases in each group. All patients receive routine nursing during hospital stay, and those in the observation group were given humanistic care with TCM nursing interventions including TCM techniques, emotional care and dietary guidance. A self-made humanistic care needs questionnaire was used to investigate the patient satisfaction with nursing service. Results Nursing satisfaction rate in the observation group was higher than that in the control group, with a significant difference (P＜0. 05). Conclusion The establishment of TCM humanistic care and nursing model in the orthopedic ward can improve patient satisfaction by identifying the needs of patients for humanistic care, taking advantages of TCM nursing and providing targeted and individualized humanistic care. (目的 探讨骨科病房中医人文关怀护理模式的构建和实施效果。方法 选取科室收治的住院患者120为研究对象, 随机分为对照组与观察组, 各60例。对照组采用医院骨科常规护理, 观察组在对照组基础上, 通过建立中医人文关怀护理模式, 实施中医护理技术、生活起居护理、情志护理、饮食护理等中医特色护理干预。采用自制住院患者护理人文关怀需求调查量表评价患者满意度。结果 观察组患者满意度高于对照组, 差异有统计学意义(P＜0. 05)。结论 在骨科病房建立中医人文关怀护理模式, 明确患者的人文关怀需求, 发挥中医护理优势, 有针对性、个体化施护人文关怀, 能够满足患者需求, 提高患者住院满意度。)